Culture is Bad for You: Inequality in the Cultural and Creative Industries by Orian Brook, Dave O’Brien and Mark Taylor, Manchester University Press (2020) - Cronin, Maggie (Irish Journal of Arts Management and Cultural Policy, 2022)
In Culture is Bad for You: Inequality in the Cultural and Creative Industries, (Manchester University Press, 2020), authors Orian Brook, Dave O’Brien and Mark Taylor cut through a Gordian Knot of interconnected and complex factors that create and maintain multiple inequalities within the UK Creative and Cultural Industries (CCIs). Exhaustive research in micro and macro detail is presented over eleven chapters, drawn from a wide range of sources. This includes previous research projects that the core group of authors and others have produced including Panic! (2018), statistical evidence, surveys and longitudinal data. It also includes qualitative data in the form of extensive interviews with cultural and creative industry workers. The result is as much a manifesto for change as well as a valuable addition to scholarship countering the ‘celebratory discourse’ in relation to the CCIs over the past 25 years. (Friedman et al, 2017; McRobbie, A. 2016; Conor et al 2015; Gill, R., 2011).